Dissolved trace metals (Ni, Zn, Co, Cd, Pb, Al, and Mn) around the Crozet Islands, Southern Ocean - Castrillejo, Maxi; Statham, Peter J.; Fones, Gary R; Planquette, Hele`ne; Farah Akmal, Binti Idrus; Roberts, Keiron (American Geophysical Union, 2013)
A phytoplankton bloom shown to be naturally iron (Fe) induced occurs north of the Crozet Islands (Southern Ocean) every year, providing an ideal opportunity to study dissolved trace metal distributions within an island system located in a high nutrient low chlorophyll (HNLC) region. We present water column proﬁles of dissolved nickel (Ni), zinc (Zn), cobalt (Co), cadmium (Cd), lead (Pb), aluminium (Al), and manganese (Mn) obtained as part of the NERC CROZEX program during austral summer (2004–2005). Two stations (M3 and M1) were sampled downstream (north) of Crozet in the bloom area and near the islands, along with a control station (M2) in the HNLC zone upstream (south) of the islands. The general range found was for Ni, 4.64–6.31 nM; Zn, 1.59–7.75 nM; Co, 24–49 pM; Cd, 135–673 pM; Pb, 6–22 pM; Al, 0.13–2.15 nM; and Mn, 0.07–0.64 nM. Vertical proﬁles indicate little island inﬂuence to the south with values in the range of other trace metal deprived regions of the Southern Ocean. Signiﬁcant removal of Ni and Cd was observed in the bloom and Zn was moderately correlated with reactive silicate (Si) indicating diatom control over the internal cycling of this metal. Higher concentrations of Zn and Cd were observed near the islands. Pb, Al, and Mn distributions also suggest small but signiﬁcant atmospheric dust supply particularly in the northern region.